Aluminium-doped TiO2 nanotubes with enhanced light-harvesting properties. Issue 13 (1st July 2021) - Puga, M.L.; Venturini, J.; Guaglianoni, W.C.; Ruwer, T.L.; Wermuth, T.B.; Bergmann, C.P.
Abstract: Titanium dioxide (TiO2 ) application in light-harvesting processes is hindered by its wide band gap. Strategies such as morphology shifts from nanoparticles to nanotubes and doping of fabricated nanostructures are widely used to address this issue. Combining both approaches, this work successfully synthesizes, for the first time, aluminium-doped TiO2 nanotubes via a single-step anodization method at three distinct potentials (20, 40 and 60 V). SEM images revealed the successful formation of remarkably thin layers of TiO2 nanotubes produced at 40 and 60 V. X-ray diffractograms and Raman spectra suggest the successful insertion of aluminium into the anatase lattice. Diffuse reflectance confirmed the doping process through a marked effect on the absorbance of visible light for the higher voltages, as well as through a reduction in the optical band gap. For utilization purposes, the photoelectrochemical performance of 40 V Al–TiO2 was able to deliver a comparable response to that of a compact TiO2 layer of the same thickness. The current density developed by the 60 V sample was increased by 120% in comparison to the undoped material, despite having an absorbance much lower than that of the latter. Overall, synthesizing an Al-doped TiO2 nanotubular structure has proven to be a great strategy in the development of materials for application in advanced light-harvesting electrodes.